2022
DOI: 10.1111/ssqu.13219
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐choice/pro‐elección versus pro‐life/pro‐vida: Examining abortion identity terms across English and Spanish in the United States

Abstract: Objective: We examine how a sample of English-and Spanishspeaking U.S. adults define the terms pro-life/pro-vida and prochoice/pro-elección and explore whether definitions differ by language and/or ethnicity. Methods: We asked a sample of 1504 English-and Spanishspeaking U.S. adults to define the terms pro-choice/pro-elección and pro-life/pro-vida in an open-ended format. We used content and thematic analysis to examine congruence and discordance between how English and Spanish speakers, as well as Latinx and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…2020; Jozkowski, Crawford, and Willis 2021; Solon et al. 2022), this study provides initial evidence for other potential factors that researchers may consider when developing abortion attitude items. Developing items that consider novel frameworks and contexts has the potential to expand measures used presently in national polls and surveys to uncover more nuance in attitudes that exists within the “murky middle.”…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…2020; Jozkowski, Crawford, and Willis 2021; Solon et al. 2022), this study provides initial evidence for other potential factors that researchers may consider when developing abortion attitude items. Developing items that consider novel frameworks and contexts has the potential to expand measures used presently in national polls and surveys to uncover more nuance in attitudes that exists within the “murky middle.”…”
Section: Discussionmentioning
confidence: 62%
“…Yet, we also found that other factors are relevant to people when conceptualizing abortion attitudes such as gestation duration as a relevant context or considering abortion relative to parenting as a potential framework. Heeding others' recommendation for more nuanced measures to assess abortion attitudes (e.g., Bruce 2020;Crawford, LaRoche, and Jozkowski 2022;Hans and Kimberly 2014;Jelen and Wilcox 2003;Jozkowski, Crawford, and Hunt 2018;Jozkowski et al 2020;Jozkowski, Crawford, and Willis 2021;Solon et al 2022), this study provides initial evidence for other potential factors that researchers may consider when developing abortion attitude items. Developing items that consider novel frameworks and contexts has the potential to expand measures used presently in national polls and surveys to uncover more nuance in attitudes that exists within the "murky middle.…”
Section: Implications For Abortion Attitude Measurementmentioning
confidence: 79%